Magnetotelluric Sampling and Geoelectric Hazard Estimation: Are National‐Scale Surveys Sufficient?. Issue 7 (13th July 2021) - Murphy, Benjamin S.; Lucas, Greg M.; Love, Jeffrey J.; Kelbert, Anna; Bedrosian, Paul A.; Rigler, E. Joshua
Abstract: At present, the most reliable information for inferring storm‐time ground electric fields along electrical transmission lines comes from coarsely sampled, national‐scale magnetotelluric (MT) data sets, such as that provided by the EarthScope USArray program. An underlying assumption in the use of such data is that they adequately sample the spatial heterogeneity of the surface relationship between geomagnetic and geoelectric fields. Here, we assess the degree to which the density of MT data sampling affects geoelectric hazard assessments. For electrical transmission networks in each of four focus regions across the contiguous United States, we perform two parallel band‐limited (10 1 –10 3 s) hazard analyses: one using only USArray‐style (∼70‐km station spacing) MT data, and one incorporating denser (≪70‐km station spacing) MT data. We find that the use of USArray‐style MT sampling alone provides a useful first‐order estimate of integrated geoelectric fields along electrical transmission lines. However, we also find that the use of higher density MT data can in some areas lead to order‐of‐magnitude differences in line‐averaged electric field estimates at the level of individual transmission lines and can also yield significant differences in subregional hazard patterns. As we demonstrate using variogram plots, these differences reflect short‐spatial‐scale variability in Earth conductivity, which in turn reflects regional lithotectonic structure and history. We also provide a cautionary example in the use of electrical conductivity models to predict dense MT data; although valuable for hazard applications, models may only be able to reproduce surface geoelectric fields as captured by the MT data from which they were derived. Plain Language Summary: Intense geomagnetic disturbances can drive large electrical currents in grounded technological infrastructure with deleterious effects. In the case of national power grids, a 1‐in‐100‐year event could cause widespread failure of long‐distance electrical distribution networks. The magnitude of these electrical currents and their associated electric fields depends crucially on how the Earth conducts electricity beneath transmission lines; as the Earth's electrical conductivity structure can spatially vary dramatically, the degree of this geoelectric hazard varies geographically. Many recent studies have utilized magnetotelluric (MT) measurements that are made several tens of kilometers apart to examine spatial patterns in hazard levels. Because the Earth's electrical conductivity structure can vary substantially at shorter length scales, we examine the degree to which higher density MT data coverage changes geoelectric hazard estimates. We find that coarse‐scale MT data, as used in previous studies, provide a valuable and generally valid estimate of regional hazard patterns. However, we also find that denser data can yield large differences (up to an order of magnitude) in hazard estimates at the level of individual electrical transmission lines. Therefore, coarse data coverage is valuable for first‐order hazard estimates, but denser data coverage can provide useful refinements to those estimates. Key Points: National‐scale magnetotelluric surveys (e.g., ∼70 km station spacing) provide a useful first‐order estimate of geoelectric hazards Higher density magnetotelluric data coverage can yield local order‐of‐magnitude differences in hazard estimates in some settings Lithotectonic structure, which dictates lithospheric electrical conductivity, controls the spatial scale of geoelectric field variability